Cathepsin D as an indicator of clinical outcome in early breast carcinoma during the first 3 years of follow-up. (October 2013) - Markićević, Milan; Kanjer, Ksenija; Mandušić, Vesna; Buta, Marko; Nešković-Konstantinović, Zora; Nikolić-Vukosavljević, Dragica
Aim: The aim of this study was to evaluate clinical usefulness of cathepsin D status in early breast cancer during the first 3 years of follow-up.Patients & methods: The study included 226 patients with histologically verified, primary operable invasive early breast carcinomas. Concentrations of estrogen receptor (ER) and progesterone receptor (PR) in breast tumor cytosols were measured by use of the classical biochemical method. The concentration of three cathepsin D forms (52-, 48- and 34-kDa proteins) was determined by a radioimmunoassayResults: On the basis of differences in cathepsin D levels either within an ER - /PR - phenotype or between this and either ER + /PR + or ER + /PR - phenotypes, a concentration of 39 pmol/mg was determined as the cutoff value for distinguishing estrogen-regulated cathepsin D expression. Estrogen-regulated cathepsin D expression was recognized as a high-risk biomarker for low-risk (histological grade I) breast cancer patients and as a low-risk biomarker for high-risk patients (pN + pT2, 3).Conclusion: Determination of cathepsin D status in breast cancer might identify patients at different risk for relapse and might facilitate the selection of more or less aggressive adjuvant therapy for early breast cancer patients during the first 3 years of follow-up.